1973
DOI: 10.1007/bf00309136
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the nature of genetic divergence in rice from assam and North East Himalayas

Abstract: A representative group of 190 rice types collected from North-East India along with four standard varieties, three of which were indicas and one japonica, was studied to understand the nature of genetic divergence. Preliminary grouping was done by canonical analysis and the resultant 42 groups were further classified using the D(2) statistic.The final grouping resulted in nine divergent clusters. The three indica standards were found in three different clusters indicating the wide available variability among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Analysis of rice accessions, both aromatic and non-aromatic, from NE Indian states revealed 2–4 clusters. Based on morphological analysis, Vairavan et al [39] reported three clusters within a set of 400 accessions from NE India. Similar grouping was obtained by analysing 6,984 NE Indian rice accessions using SNP markers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of rice accessions, both aromatic and non-aromatic, from NE Indian states revealed 2–4 clusters. Based on morphological analysis, Vairavan et al [39] reported three clusters within a set of 400 accessions from NE India. Similar grouping was obtained by analysing 6,984 NE Indian rice accessions using SNP markers [33].…”
Section: Discussionmentioning
confidence: 99%
“…This includes different ecosystem based on occurrence such as upland, lowland, deep-water varieties and their wild relatives. The landraces grown at high elevations of 2000-2500 m of Arunachal Pradesh very much resemble Japonica plant and grain as well as intermediate types (Vairavan et al 1973). Seetharaman et al (1974) found that not only isolated characters but whole constellation of Japonica characters such as thin culm, low tillering, short panicle etc.…”
Section: Resultsmentioning
confidence: 97%
“…The frequency of fine grain types among Arunachal Pradesh landraces except Kameng and Subansiri districts ranged from 9-32% (Sharma 1982). Vairavan et al (1973) studied the nature of genetic divergence in 190 landraces belonging to northeastern India and classified them into nine clusters and concluded that some of the clusters occupied intermediate positions between japonica and indica. But Srivastava and Nanda (1977) recognized five groups in the collections from northeastern India and attributed genecological differentiation for a constellation of characters identifying each group.…”
Section: Relevance and Importancementioning
confidence: 99%
“…Although a few studies have examined the population genetic structure of O. sativa germplasm at a global scale (Glaszmann 1987; Garris et al 2005), region specific studies are limited. Earlier studies based on morphology and agronomic traits (Vairavan et al 1973; Borkakati et al 2000; Sarma and Pattanayak 2009) as well as molecular markers (isozyme, RAPD, ISSR) demonstrated a high level of genetic diversity among indigenous rice varieties in NE India (Glaszmann et al 1989; Sarma and Bahar 2005; Bhuyan et al 2007). However, these studies were limited either to a particular group of varieties ( e.g.…”
Section: Introductionmentioning
confidence: 99%